Some results in probabilistic n-Banach spaces - Salimi, Mehdi; Pourmoslemi, Alireza; Ismail, Fudziah (Pushpa Publishing House, 2009)
In this article, after introducing the probabilistic n-normed spaces we define probabilistic n-Banach spaces and study convergence in these spaces by some theorems.